Monitoring the Subolesin Vaccine Field Trial for Safer Control of Cattle Ticks Amidst Increasing Acaricide Resistance in Uganda - Kabi, Fredrick; Dhikusooka, Moses; Matovu, Moses; Mugerwa, Swidiq; Kasaija, Paul; Emudong, Patrick; Kirunda, Halid; Contreras, Marinela; Gortazar, Christian; De la Fuente, Jose (Vaccines, 2022)
A collaboration program was established between the group of Health and Biotechnology (SaBio) of the IREC Institute of Game and Wildlife Research (CSIC-UCLM-JCCM, Spain) and the National Agricultural Research Organization of Uganda (NARO) for the development of vaccines for the control of cattle ticks in Uganda. Controlled pen trials identified a tick protective antigen, Rhipicephalus appendiculatus Subolesin, and a cross-species-effective vaccine formulation. As the next step, a controlled vaccine field trial has been approved by Ugandan state regulatory authorities, the Uganda National Council for Science and Technology (UNCST) and the National Drug Authority (NDA), to evaluate the efficacy and effectiveness of the vaccine formulation for the control of cattle tick infestations under field conditions. The results of this trial may lead to the approval of the vaccine for application in Uganda to improve cattle health and production while reducing the use of acaricides.
Keywords: Subolesin; Vaccine; Cattle; Tick; Field trial; Introduction